Nanosecond pulsed laser ablation to synthesize GaO colloidal nanoparticles: Optical and structural properties - Al-Douri, Yarub; Al-Samarai, Riyadh A.; Abdulateef, Sinan A.; Odeh, Ali Abu; Badi, Nacer; Voon, Chun Hong (Elsevier, 2019)
Pulsed laser ablation (PLA) has been employed to prepare GaO colloidal nanoparticles to investigate the optical and structural properties using ultraviolet–visible (UV–vis) absorption spectrophotometer, X-ray diffraction (XRD) and Tunneling Electron Microscopy (TEM) instruments, respectively under different laser fluences. Image processing method of TEM images and XRD scheme is used to examine the nanoparticle's mean size and size distribution. Laser fluence has proved its significant effect on the size of nanoparticles. In addition, nanoparticle's mean size and size distribution have undergone under effect of ablation process. It has been resulted that nanoparticle's larger size distribution and mean size have been produced by higher laser fluences.